2022
DOI: 10.1186/s12872-022-02657-y
|View full text |Cite
|
Sign up to set email alerts
|

The pre-ablation triglyceride-glucose index predicts late recurrence of atrial fibrillation after radiofrequency ablation in non-diabetic adults

Abstract: Background Current prognostic risk scoring systems and biomarkers are routinely used as non-invasive methods for assessing late recurrence of atrial fibrillation (AF) in patients who have undergone radiofrequency catheter ablation (RFCA). This study aimed to investigate the predictive value of the triglyceride-glucose (TyG) index for late AF recurrence after RFCA in non-diabetic patients. Methods In total, 275 patients with AF who underwent RFCA at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Moreover, since different cohorts may lead to the controversial results, an additional subgroup analysis of our study compared the difference between diabetic and non-diabetic population. Similar to what published researches reported (26,29,30), the present study showed the elevated TyG index was associated with AF in non-diabetic, whereas a role between TyG index with AF has not been observed in diabetic subjects. Lee et al have identified the non-linear relationship between IR and the risk of AF, and the AF development increased at the HOMA-IR levels approximately between 1-2.5, and then plateaued afterwards (6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, since different cohorts may lead to the controversial results, an additional subgroup analysis of our study compared the difference between diabetic and non-diabetic population. Similar to what published researches reported (26,29,30), the present study showed the elevated TyG index was associated with AF in non-diabetic, whereas a role between TyG index with AF has not been observed in diabetic subjects. Lee et al have identified the non-linear relationship between IR and the risk of AF, and the AF development increased at the HOMA-IR levels approximately between 1-2.5, and then plateaued afterwards (6).…”
Section: Discussionsupporting
confidence: 92%
“…found the baseline IR contributes to the long-term risk of incident AF in a community-based non-diabetes population ( 6 ). And a retrospective study of non-diabetic patients who have undergone radiofrequency catheter ablation (RFCA) showed the elevated TyG index was associated with an increased risk of late AF recurrence ( 26 ). Data from animal experiment also shows the IR mice were highly vulnerable to AF due to impaired glucose transport in the atria ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary vein isolation (PVI) is an essential approach, and its electric isolation from the left atrium (LA) achieves a high rate of freedom from AF. However, AF recurrence often occurs, which is not only due to pulmonary vein (PV) reconnection but also an additional arrhythmogenic atrium responsible for AF maintenance [1,2]. Atrial substrate remodeling progresses with aging, the persistence of AF, heart failure, and cardiovascular risk factors [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this study demonstrated that METS-IR could predict AF recurrence, with the higher predictive value compared with TyG index and TG/HDL-C ratio. Recent research showed that an elevated pre-ablation TyG index is associated with an increased risk of AF recurrence after RFCA in non-diabetic patients [ 35 ]. We demonstrated that TyG index was an independent risk factor for recurrence after AF ablation, both in diabetic and non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IR induces structural remodelling of the atria and abnormal intracellular calcium homeostasis [ 46 ]. Increased oxidative stress and inflammation were associated with impaired IR and insulin secretion, resulting in atrial electrical remodeling, LA fibrosis and LA low-pressure area, which may be the main components of the pathophysiology of AF [ 35 , 47 ]. Most components of IR, such as abnormal glucose tolerance, obesity, and abnormal lipid levels, have been found to have a cumulative effect on the risk of AF progression, which may be associated with AF recurrence after RFCA.…”
Section: Discussionmentioning
confidence: 99%